(untitled) (Bangladesh Journal of Medical Science, 2020)
Introduction: Acute Kidney Injury is characterized by an acute and potentially reversible deterioration of renal function, which results in failure of the kidney to excrete nitrogenous waste products and to maintain fluid and electrolyte balance. There is marked variation in epidemiological data of Acute Kidney Injury depending upon the definitions used, population being studied and the clinical settings. Aims and Objectives: This study was designed to determine the clinical profile of adult patients with Acute Kidney Injury (AKI) admitted in the medical ICU at a rural tertiary care centre in North India. Materials and Methods: This prospective observational study was conducted on 70 patients of Acute Kidney Injury admitted in the Medical Intensive Care Unit in Department of Medicine at M. M. Institute of Medical Sciences and Research, Mullana, Ambala. AKI was diagnosed and staged for severity according to the KDIGO criteria. Results and Observations: Amongst the 70 cases of AKI, 32 cases (45.7%) were females while 38 cases (54.3%) were males. The mean age at presentation was 55.22 ± 14.91 years. Sepsis was found to be the major cause of AKI. Out of 70 patients in our study, 45 (64.2%) cases were attributed to sepsis. Mortality rate seen in this study was 40% (n=28). Conclusion: Acute Kidney Injury is a common clinical problem encountered in critically ill patients, especially in the medical ICU. Early detection and adequate management is important to reduce AKI related as well as all- cause mortality in critically ill patients. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.685-691